2022
DOI: 10.1038/s41419-022-05431-2
|View full text |Cite
|
Sign up to set email alerts
|

Translational readthrough of nonsense mutant TP53 by mRNA incorporation of 5-Fluorouridine

Abstract: TP53 nonsense mutations in cancer produce truncated inactive p53 protein. We show that 5-FU metabolite 5-Fluorouridine (FUr) induces full-length p53 in human tumor cells carrying R213X nonsense mutant TP53. Ribosome profiling visualized translational readthrough at the R213X premature stop codon and demonstrated that FUr-induced readthrough is less permissive for canonical stop codon readthrough compared to aminoglycoside G418. FUr is incorporated into mRNA and can potentially base-pair with guanine, allowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…The ochre suppression clonal cell lysate also featured a distinct band, suggesting a particularly strongly labeled endogenous protein. It is interesting to note, that endogenous opal codons do not appear to be more efficiently suppressed by tRNA Pyl than the other two stop codons, despite the opal codon being known to show highest leakiness, i.e., readthrough with endogenous tRNAs 33,39,40 . In summary, productive ochre and opal suppression is possible to achieve in stable settings.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The ochre suppression clonal cell lysate also featured a distinct band, suggesting a particularly strongly labeled endogenous protein. It is interesting to note, that endogenous opal codons do not appear to be more efficiently suppressed by tRNA Pyl than the other two stop codons, despite the opal codon being known to show highest leakiness, i.e., readthrough with endogenous tRNAs 33,39,40 . In summary, productive ochre and opal suppression is possible to achieve in stable settings.…”
Section: Resultsmentioning
confidence: 98%
“…It is interesting to note, that endogenous opal codons do not appear to be more efficiently suppressed by PylT than the other two stop codons, despite the opal codon being known to show highest leakiness, i.e. readthrough with endogenous tRNAs (Floquet et al 2012; Schmied et al 2014; Palomar-Siles et al 2022). In summary, productive ochre and opal suppression is possible to achieve in stable settings.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, 5-Fluorouridine (FUr) was identified in a data mining effort of 47,000 anti-cancer drugs as potent readthrough-inducing compound [ 121 ]. Specifically, a search of the NCI-60 database for substances that suppress growth of a subset of tumor cells carrying p53 nonsense mutations (e.g., TP53 R213* UGA PTC) yielded 28 candidate compounds, among these the widely used anti-cancer drug 5-Fluorouracil (5-FU).…”
Section: Induction Of Nonsense Suppressionmentioning
confidence: 99%
“…Follow-up experiments revealed that the 5-FU metabolite 5-Fluorouridine (FUr) was the actual readthrough-inducing compound. FUr exerted its effect by direct incorporation into nonsense-bearing TP53 mRNA, where it facilitated the readthrough of the PTC but not of the canonical stop codon (as shown by Ribo-seq) [ 121 ]. Tests employing mutated superfolder GFP with a UGA, UAG or UAA PTC at position 150 further demonstrated that FUr induced readthrough of UGA or UAG but not UAA.…”
Section: Induction Of Nonsense Suppressionmentioning
confidence: 99%
“…This results in the production of abnormal RNAs (e.g., through altered splicing) 2 , aberrant post-transcriptional modifications (e.g. pseudo-uridylation) 7 , alteration of ribosome biogenesis or functions 8 , and aberrant translation-dependent events (e.g., stop-codon readthrough) 4,8 . However, the underlying mechanistic details of RNA-dependent 5FU cytotoxicity remains ill-defined 9 .…”
Section: Introductionmentioning
confidence: 99%